The Influence of Self-Regulation on General Self-Efficacy: The Mediating Role of Mental Well-Being among University Students - Mayenti , Yelvia Septi; Zahra, Faradilla Asyifa; Hakam, Kama Abdul; Malihah, Elly; Mupid (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Mental health has become a pressing issue in higher education, with university students increasingly vulnerable to stress, anxiety, and reduced academic engagement. While self-regulation and general self-efficacy are recognized as key determinants of academic adjustment, the mechanisms linking these constructs remain underexplored. This study investigates the influence of self-regulation on general self-efficacy, emphasizing the mediating role of mental well-being among university students. A total of 380 valid responses were collected from undergraduate students in Pekanbaru, Indonesia, using validated scales for self-regulation, mental well-being, and general self-efficacy. Structural Equation Modeling (SEM) with AMOS 26 was employed to test the hypothesized relationships. The findings reveal that self-regulation significantly predicts both mental well-being and general self-efficacy. Furthermore, mental well-being demonstrates a positive and significant mediating effect on the relationship between self-regulation and general self-efficacy. These results underscore the importance of mental well-being as a psychological resource that strengthens the pathway between self-regulatory competence and efficacy beliefs. Theoretically, this study extends self-regulated learning models by integrating mental health as a mediating construct, while practically, it highlights the need for higher education institutions to design interventions that foster both self-regulatory skills and psychological well-being. By positioning mental well-being as both an outcome of self-regulation and a driver of self-efficacy, the study provides actionable insights for enhancing student resilience and academic success, particularly in the post-pandemic era